Methicillin resistant Staphylococcus aureus contamination of phlebotomy tourniquets and faucets - Abeywickrama, T; Amarasinghe, K; Wijerathne, S; Dharmarathne, C; Fernando, D; Senaratne, B.C.V; Gunasekara, H.A.K.M (Ceylon Medical Journal, 2018)
Introduction Methicillin resistant Staphylococcus aureus (MRSA) is transmitted through direct contact or fomites. The most important means of nosocomial spread is by hospital personnel. However, fomites are being increasingly recognized as sources of nosocomial infection. Objectives Our aim was to describe the MRSA contamination rate of phlebotomy tourniquets and faucets in a tertiary care hospital and to compare the contamination of plastic tourniquets with that of fabric tourniquets. Method A cross-sectional study was carried out in the general wards of a tertiary care hospital in the Colombo District. Two hundred tourniquets were collected and 100 faucets were swabbed and cultured on CHROMagar™ MRSA medium (CHROMagar Microbiology). Contamination rates of 50 plastic tourniquets and 50 fabric tourniquets were compared. Results MRSA grew in 26% of tourniquets. Majority were plastic tubes. MRSA contamination of tourniquets did not significantly differ by ward (p>0.4). MRSA was found on 26% of faucets. Contamination rate was highest in the common wards for dermatology, dental, rheumatology, and neurology (55.6%), followed by gynaecology (45.2%), cardiology (33.3%), surgery (18.8%), psychiatry (11.1%), and medicine (5.6%). There was a significant difference in rates of contamination of faucets in the different wards (p<0.01). There was no significant difference in the colony count per surface area of the two types of tourniquets after a single use. Conclusions MRSA contamination rates of tourniquets and faucets were high. Single-use new plastic tourniquets were much less contaminated with MRSA than reused tourniquets.